Dormancy breaking and germination of Enterolobium contortisiliquum (Vell.) Morong seed - Ubirajara Contro Malavasi; Marlene de Matos Malavasi (Brazilian Archives of Biology and Technology, 2004)
Enterolobium contortisiliquum (Vell.) Morong. is a Mimosaceae tropical tree species recommended for heterogeneous reforestation of degraded tropical areas. "Timburi" seeds present low germination due to the high degree of seed dormancy. Different methods to overcome seed dormancy was compared: sanding, sanding followed by 24 hours water (25ºC) soaking, imbibition in boiling water followed by exposure to water at room temperature (28ºC), and concentrated sulfuric acid (5, 15, 30, 60, 120 or 180 minutes) followed by washing with tap water. All seeds were germinated in rolled towels at 25ºC and 12 hours photoperiod. Total germination, first count of germination test and germination velocity index were recorded. Mechanical scarification (sanding), chemical scarification (treatment with acid for 30, 60, 120 or 180 minutes) and mechanical scarification followed by cold water imbibition were efficient in promoting germination. For practical purposes, mechanical scarification is highly recommended for forest nurseries. Enterolobium contortisiliquum (Vell.) Morong. é uma espécie arbórea tropical recomendada para reflorestamentos heterogêneos de áreas degradadas. Sementes de timburi apresentam baixa germinação causada pela dormência das sementes. Diferentes métodos de superação da dormência das sementes foram comparados: lixa, lixa seguida por embebição em água (25ºC) por 24 horas, embebição em água fervente seguida por embebição em água a temperatura ambiente (28ºC), e ácido sulfúrico concentrado (5, 15, 30, 60, 120 ou 180 minutos) seguido de lavagem com água corrente. Todas as sementes forma germinadas em rolos de papel a 25ºC e fotoperíodo de 12 horas. Germinação total, primeira contagem do teste de germinação e índice de velocidade de germinação foram anotados. Escarificação mecânica (lixa), escarificação química (tratamento com ácido por 30, 60, 120 ou 180 minutos) e escarificação mecânica seguida de embebição em água fria foram eficientes em promover a germinação. Por razões práticas, escarificação mecânica é altamente recomendável para viveiros florestais.